Corporate governance and financial distress: An endogenous switching regression model approach in vietnam - Khiem Dieu Truong (Cogent Economics & Finance, 2022)
This study aims to determine the impact of Corporate Governance on the relationship between the macro and micro factors causing financial distress in 240 Vietnamese listed non-financial firms. The study also investigates the marginal benefits of different corporate governance practices by applying an endogenous switching regression model (ESRM). The research clarifies that a firm with strong corporate governance practice has a low probability of financial distress compared to a weak corporate governance firm. Moreover, the risk of financial distress is significantly reduced when improving the corporate governance practice. This paper contributes empirical evidence on the predominant benefit of strong corporate governance practices and marginal benefit in risk mitigation in enhancing corporate governance. The article suggests that Vietnamese firms should implement strong corporate governance to overcome the risk of financial distress.
Keywords: G34; G32; 330; Corporate governance; financial distress; emerging countries; endogenous switching regression